Effects of Tumescent Solution on Fat Survival - ERCAN, FERİHA; KAYA, ÖZLEM TUĞÇE (THIEME MEDICAL PUBL INC, 2017)
Autologous fat transfer is a commonly used procedure in plastic surgery practice. The long-term survival rate of fat grafts is the most important issue for satisfactory results. The presented study includes the effects of different tumescent solutions on long-term fat graft survival. A total of 24 rats were divided into four groups: sham, lidocaine, adrenaline, and lidocaine + adrenaline groups. In all groups except the sham group, right inguinal fat pad was harvested 10 minutes after injecting 5 cc of the appropriate tumescent solution. The fat pad was trimmed and reimplanted to the interscapular area. After 3 months, fat pad was reharvested and sent for histopathologic evaluation. The harvested fat grafts were weighted in both surgical sessions. A significant difference was observed in comparison of fat grafts weights between the initial operation and the postoperative third month (p = 0.002). By intergroup comparisons, a significant difference was observed between sham and adrenaline groups (p = 0.002) and between sham and lidocaine + adrenaline groups (p = 0.007). No statistical difference was observed by the comparison of TUNNEL results (p = 0.663). The histopathologic evaluation of the specimens revealed similar results between groups. The injection of tumescent solutions containing only lidocaine before fat harvesting yields similar long-term fat graft survival rates in comparison to the conduction of surgical procedure without injecting any tumescent fluid. However, the injection of solutions containing adrenaline with or without lidocaine may decrease the long-term survival rates of fat autografts.
Keywords: liposuction; autologous fat transfer; tumescent solution; fat graft survival; GRAFT-SURVIVAL; EPINEPHRINE; LIDOCAINE; TERM